Broadcom´s failed acquisition of qualcomm - an analysis of the strategic rationale and business model implications - Goßmann, Andreas (2023)
In November 2017, Broadcom made an initial bid to take over its competitor Qualcomm, a US based semiconductor company, to create one of the largest technology enterprises worldwide in a deal that raised concerns about regulatory approval right from the start. The case examines the situation at the beginning of March 2018 after Broadcom had already made two revised bids and analyzes different angles to give a comprehensive overview of the acquisition. The individual part analyzes the strategic rationale and motives for the deal. The analysis includes the product and strategic fit of both businesses, the pros and cons of the strategic rationale and respective post-merger implications and potential CEO biases at play to eventually answer the question whether the deal is driven by sustainable reasons. The aim of this case is to better understand the multiple facets of cross-border M&A deals and the different parameters influencing the feasibility.